Hypertension Prevalence Rates Among Urban and Rural Older Adults of China, 1991–2015: A Standardization and Decomposition Analysis - Yu, Qi; Lin, Shiqi; Wu, Jilei (Frontiers in Public Health, 2021)
Objectives:We aimed to assess the urban-rural gaps in trends of hypertension rates in elderly, and found the crucial contributing factor of hypertension rates in China during 1991-2015. Methods: We performed several national cross-sectional analyses for hypertension based on China Health and Nutrition Survey (CHNS) data.This study compared the hypertension rates between urban and rural elderly population with the standardization and decomposition analysis, and calculated the factor-specific rates and contributions of each demographic and social development compositions (age, gender, education, region). Results: The hypertension rates of both urban and rural elderly population were on the rise, with the rates in urban area higher than rural area throughout 1991-2015. Gaps between the urban and rural elderly exhibited narrower than without adjustment for crude rate, and showed a dynamic change characteristic, which presented a decreasing trend during 1993-1997, an expanding trend during 1997-2011, and a decreasing trend during 2011-2015 again. Compared with other components with a stable and low contribution trend, region was the factor that contributed the most to hypertension rates, and its impact was still on the rise. Conclusions: With the development of social economy and the acceleration of population aging, the influence of demographic factors such as age and education on hypertension rates is becoming stable. Instead, regional differences have an increasing impact on the hypertension rates. It suggests that policy makers should pay more attention to the differences between rural and urban rather than demographic factors when making health policy.